Pengembangan Game Edukasi RPG Petualangan 2D tentang Peristiwa Lautan Api Bandung Menggunakan Alur Cerita Naratif Bercabang - Sabda Sankalla; Chrystia Aji Putra; Andreas Nugroho Sihananto (bit-Tech, 2026)
This study evaluates the effectiveness of a 2D educational adventure RPG integrating branching narratives and a Numberlink-based puzzle to enhance students’ understanding of the historical Bandung Lautan Api event. Addressing the persistent issue of low engagement in history classrooms, the research investigates whether interactive storytelling and embedded logic-puzzle tasks can strengthen learning outcomes and user experience. Using a design-based research approach, the game was tested with 23 junior high school students through a pre-test/post-test design and the Game User Experience Satisfaction Scale (GUESS-18). The results show a substantial increase in historical knowledge, with post-test scores significantly higher than pre-test scores, indicating strong knowledge acquisition following gameplay. GUESS-18 responses also reveal consistently positive user experiences, with high ratings for narrative quality, educational value, visual and audio aesthetics, and overall enjoyment. Students reported that branching choices improved immersion and reflective thinking, while the Numberlink puzzle supported active reasoning during missions. These findings demonstrate that the integration of interactive narrative structures and logic-based puzzles can effectively support both cognitive and affective dimensions of history learning. Overall, the study confirms the potential of game-based learning to enhance comprehension, motivation, and engagement, providing evidence that well-designed educational games can significantly improve learning performance and serve as a valuable supplement to conventional history instruction.